Strategies for the internationalization of education and curriculum: From universities to territories of basic education - Thiesen, Juarues da Silva (Education Policy Analysis Archives, 2019)
The objective of the study is to analyze implications of the movements for the curricular internationalization of higher education in terms of current curriculum policies and reconfigurations of basic education, particularly in Brazil and Portugal. This article presents and discusses a set of strategies that have been formulated and or adopted by the Brazilian state and by non-state organizations that seek to align higher education and basic education curriculums to movements that defend internationalization. Drawing on previous research, this exploratory and empirical study uses official texts of Brazilian educational and curricular policy, as well as projects of private institutions related to curriculum internationalization, as its primary sources. The article concludes that there is a significant process of alignment of Brazilian education to the expectations and demands of internationalization and that various strategies adopted in higher education are readapted for use in curricular territories of basic education.